CLAY MODELLING INDUSTRY AND ITS PROBLEMS: A CASE STUDY OF THE GHURNI REGION - Mondal, Pijus Kanti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The clay craft of Ghurni, renowned for its intricate artistry, faces multiple issues threatening its survival. Through an extensive survey and data analysis, this study examines in detail various dimensions: the history, manufacturing process, present scenario, problems, recent changes, and prospects. It traces the roots and evolution since the 1700s, the dependence of families on this cottage industry, the socioeconomics underlying the issues, and measures by agencies to address them. Broad recommendations are presented to boost incomes, safeguard inherited skills, promote sustainable clay craft tourism, and leverage modern technology and e-commerce while retaining cultural uniqueness. Strategic collaboration of clay artisans, government bodies, designers and civil society is vital for the sector’s holistic growth.